Characterisation of lupin anthracnose caused by Colletotrichum gloeosporioides - Ghebremariam, Dawit Solomon (University of the Free State, 2001)
English: In pathogenicity studies on 14-d-old lupin seedlings, SIX isolates of C. gloeosporioides (collected in 1999 and 2000) showed no pathogenic variation on the 16 lupin cultivars tested compared to an isolate collected in 1995 at the start of the disease outbreak. L. angustifolius cultivars Wonga and Tanjil were consistently more resistant and L. albus cultvars Kiev Mutant, Swartland, CED 6150, Eisa and Vladimir were more susceptible to the seven isolates tested. This suggests that no new virulent isolates of the fungus have appeared in South Africa and that in the short term the cultivation of L. angustifolius cultvars, although L. albus cultivars is preferred, is safe from severe anthracnose attacks in this country. Continuous characterization of isolates and monitoring must however be encouraged in future in order to prevent any potential threats to the local lupin industry. By employing the barley bioassay method of Jones & Varner (1967), gibberellin-like substances were detected in liquid culture from isolates of C. gloeosporioides that cause lupin anthracnose. This is also the first time that gibberellin is associated with a Colletotrichum spp. Its role in the pathogenesis of lupin anthracnose is unknown although some studies have established a correlation between GA3 production and increased disease severity (Sunder et al., 1998) and therefore might be useful for in screening of lupin cultivars for disease resistance. As gibberillins have many modes of action (Salisbury & Ross, 1992) the role of gibberellins in this specific pathogen/host interaction must be investigated. The relationship between GA3 production by the pathogen and the typical twisting and bending of stems and petioles must also be determined. At microscopic level no qualitative differences in conidial germination, appressori urn formation or penetration of the epidermal cell wall by C. gloeosprioides in the very susceptible L. albus cv Kiev Mutant and the less susceptible L. angustifolius cv Wonga were detected. Penetration occurred directly through both the cuticle and. epidermal cell walls. In both cases small spherical vesicles with single primary hyphae were observed in the first penetrated epidermal cells. It will appear that the initial establishment of the pathogen up to vesicle formation is not related to the resistance of lupin cultivars. Post infection hyphal development up to 144 h could not be observed and might be related to an extended biotrophic relationship between the fungus and the host. Furthermore it seems like defense reactions by the plant are only activated after penetration and initial establishment of the pathogen in the host epidermis.

Afrikaans: In infeksiestudies op 14-d-oue saailinge van 16 lupienkultivars is geen variasie waargeneem tussen ses isolate van C. gloeosporioides (versamel In 1999 en 2000) en 'n isolaat versamel aan die begin van die siekte-uitbraak in 1995. Die L. angustifolius kultivars Wonga en Tanjil was deurgaans meer bestand en die L. albus kultivars Kiev Mutant, Swartland, eED 6150, Eisa en Vladirnir meer vatbaar teen die sewe isolate getoets. Dit dui aan dat geen viru1ensieverandrings in die swam voorgekom het nie en dat alhoewel L. albus verkies word, L. angustijolius kultivars tans beskerm is teen hewige antraknoseinfeksies. Voortdurende karakterisering van isolate en monitering word egter aanbeveel om die plaaslike lupienindustrie teen virulensieveranderings te waarsku. Met behulp van die garsbiotoets van Jones & Yarn er (1967) is gibberelienagtige verbindings waargeneem in vloeibare kulture van C. gloeosporioides isolate wat lupienantraknose veroorsaak. Dit is die eerste aanmelding van 'n verwantskap tussen gibberelien en Colletotrichum spp. Met die uitsondering van 'n korrelasie tussen GA] . produksie en verhoogde siektevoorkoms (Sunder et aI., 1998) is die rol daarvan in antraknose-patogenese grootliks onbekend, en kan dit moontlik van hulp wees in die evaluering van siekteweerstand. Aangesien gibbereliene baie meganismes van werking het (Salisbury & Ross, 1992) word voorgestel dat hul rol in die lupien-antraknose interaksie, met spesifieke verwysing na die verdraaiing en buiging van stamme en blaarstele, verder ondersoek word. Op mikroskopiese vlak is geen kwalitatiewe verskille in konidiumontkieming, appressoriumvorming of penetrasie van die epidermisselwande van die vatbare L. albus kv. Kiev Mutuant, en meer bestande L. angustijolius kv. Wonga, deur C. gloeosporioides gevind nie. Direkte penetrasie deur beide die kutikula en epidermiswand is waargeneem. In beide gevalle het klein, sferiese vesikels met enkel, primêre hifes in die gepenetreerde epidermisselle voorgekom. Dit het geblyk dat die aanvanklike vestiging van die patogeen nie beïnvloed is deur die weerstandsvlakke van lupienkultivars nie. Geen verder swamontwikkeling is waargeneem tot 144 h na penetrasie nie en kan dit verband hou met 'n verlengde biotrofiese verwantskap tussen die patogeen en gasheer. Dit was duidelik dat die weerstandsmeganismes eers na die aanvanklike penetrasie en vestiging van die swam in die gasheerepidermis geaktiveer word.
Keywords: Lupines -- Diseases and pests -- South Africa; Fungal diseases of plants -- South Africa; Dissertation (M.Sc.Agric. (Plant Pathology))--University of the Free State, 2002